The Generation of Human Induced Pluripotent Stem Cells from Blood Cells: An Efficient Protocol Using Serial Plating of Reprogrammed Cells by Centrifugation - Youngkyun Kim; Yeri Alice Rim; Hyoju Yi; Narae Park; Sung-Hwan Park; Ji Hyeon Ju (Stem Cells International)
Human induced pluripotent stem cells (hiPSCs) have demonstrated great potential for differentiation into diverse tissues. We report a straightforward and highly efficient method for the generation of iPSCs from PBMCs. By plating the cells serially to a newly coated plate by centrifugation, this protocol provides multiple healthy iPSC colonies even from a small number of PBMCs. The generated iPSCs expressed pluripotent markers and differentiated into all three germ layer lineages. The protocol can also be used with umbilical cord blood mononuclear cells (CBMCs). In this study, we present a simple and efficient protocol that improved the yield of iPSCs from floating cells such as PBMCs and CBMCs by serial plating and centrifugation.